GDP Development and Employment in Egypt (2000-2013) - Malec, Karel; Gouda, Shereen; Kuzmenko, Elena; Soleimani, Daryoush; Å˜ezbovÃ¡, Helena; Å Ã¡novÃ¡, Petra (International Journal of Economics and Financial Issues, 2016)
The paper is focused on unemployment in Egypt during the period 2000–2013. The unemployment is slightly increasing year by year and represents serious problem because of its structure, when it is meance mainly to young absolvents of universities, which amount is also increasing in observed period. The next analysed factor is GDP. In the paper is examined its effect on unemployment. The study also reflects the impact of Arab Spring in 2011. Data has been obtained from Central Agency for Public Mobilization and Statistics (CAPMAS), Central Bank of Egypt (CBE) and Food and Agricultural Organization of the United Nations (FAO). There have been used methods of chain inicies to reflect the development of observed indicators, and linear regression to describe the trend development. Regards the relationship of GDP and unemployment, Pearson correlation coefficient and elasticity coefficients have been used. Results show strong relationship between the GDP and unemployment in Egypt. Based on obtained data has been found, that there are needed reforms which would help to involve women and young absolvents to the job market. These changes require deet structural changes in whole economy. Keywords: Unemployment, Employment, Egypt, GDP, Value chain index, Education, Effectivness JEL Classifications: E2; R1; R100